With a Little Help from My Friends: Ministerial Alignment and Public Spending Composition in Parliamentary Democracies - Abel Bojar (London School of Economics and Political Science (LSE), European Institute, 2018)
The determinants of public spending composition have been studied from three broad perspectives in the scholarly literature: functional economic pressures, institutional constraints and party-political determinants. This paper engages with the third perspective by placing intra-governmental dynamics in the center of the analysis. Building on the portfolio allocation approach in the coalition formation literature and the common pool perspective in public budgeting, I argue that spending ministers with party-political backing from the Finance Minister or the Prime Minister are in a privileged positon to obtain extra funding for their policy jurisdictions compared to their colleagues without such support or without any partisan affiliation (non-partisan ministers). I test these propositions via a system of equations on six spending categories using seemingly unrelated regressions on a panel of 32 parliamentary democracies over two decades and offer largely supportive empirical evidence. With the exception of education, I provide evidence that budget shares accruing to key spending departments reflect this party-political logic of spending outcomes. In addition to the econometric results, I also illustrate the impact of ministerial alignment by short qualitative accounts from selected country cases.
Keywords: 330; Public spending; budget composition; cabinet; ministers; coalition